Saúde do Trabalhador: um estudo com profissionais que lidam com o sofrimento do outro na atenção domiciliar - Rezende, Laura Cristina Silva (2017)
Home Care is a modality of health care available in several countries and is related to the demographic and epidemiological transition, to the increasing costs of hospitalization, to technological development and to the processes of humanization of health and de-hospitalization. The Regulation for the Home Care under the Sistema Unico de Saude (SUS) occurred in 2002 and subsidized the implementation of programs throug the country, among which the Programa Melhor em Casa (PMC), the scenario of this research. The PMC is operated by multiprofessional teams that act in a territorialized way, focusing on dehospitalization and the involvement of caregivers. The main objective of this research was to understand the impacts of work in Home Care and the contact with the suffering of the other on the health of PMC team workers in a State of Brazil. To achieve this goal we had four objectives to support the objective: know the composition of the teams and the organization of the work; identify the way the workers understand the public served, the singularities of Home care and its impacts on workers' health; know the individual and group strategies developed to deal with the suffering generated by the coexistence with the suffering of the other, whether users or caregivers; verify the existence of governmental initiatives to promote workers' health. Triangulation of qualitative and quantitative methods was used. Data were collected using ethnography, a focus group, interviews with a semi-structured script and a self- administered questionnaire. Thirty-two (89.86%) workers, including 04 coordinators, from 10 teams which 7 were linked to the municipal government and 3 were the Federal Education Institution (IFE) participated of the study. All participants responded to the questionnaire, thirty of them participated in three focal groups and four coordinators gave interviews. Fieldwork guided the understanding of work organization in PMC and the specificities of Home Care. The descriptive statistics allowed the systematization of the data referring to the socio-demographic profile of the workers. The thematic analysis facilitated the understanding of the data obtained with GF, interviews and open question of the questionnaire. The study allowed us to glimpse the singularities of Home Care and its impacts on comprehensive health care, humanization, dehospitalization and the creation of links between workers, patients, caregivers and family members. Workers comprehend in an extended way the social determinants of health, the singularities of each patient, caregiver and family member. Every day they are affected by the health-disease-care process and by the challenges to the functioning of the system, SUS. They recognized the skills needed to work in Home Care and their specifics in relation to other institutions and programs. They were motivated to work in teams, valued collective learning and pondered the importance of recognizing their work as a source of satisfaction. Work intensity, involvement with families and their demands, challenges for SUS Network articulation and emotional overload were highlighted as impacts of work on their health condition. The perceived advances in AD are not anchored in the health promotion of workers. Such actions do not exist in the municipal government. In the IFE there are actions focused on the health of the server, but there is no participation due to other labor ties, schedules and places of supply, as well as the low adherence to self-care practices. The study revealed expectations regarding initiatives that contribute to the promotion of workers' health besides greater investments in PMC and SUS.